Well-defined poly(4-vinylbenzocyclobutene): synthesis by living anionic polymerization and characterization - Sakellariou, G.; Baskaran, D.; Hadjichristidis, Nikos; Mays, Jimmy W. (Macromolecules, 2006)
Living anionic polymerization of 4-vinylbenzocylobutene was performed in benzene at room temperature using sec-butyllithium as the initiator. Results of the kinetic studies indicated the termination- and transfer-free nature of the polymerization. Homopolymers with predictable molecular weights and narrow molecular weight distributions were produced, excluding the interference of the cyclobutene rings during initiation and propagation. Thermogravimetric analysis of poly( 4-vinylbenzocyclobutene) in air showed a small weight gain at similar to 200 degrees C, a rapid decomposition at similar to 455 degrees C, and a gradual decomposition at similar to 566 degrees C. This behavior was attributed to the formation of radicals from the pendent benzocyclobutene functionality through o-quinodimethane intermediates and simultaneous decomposition/ cross-linking reactions at high temperature. The living nature of the polymerization was also examined via sequential copolymerization with butadiene to form diblock copolymers.